Aplikasi Media Pembelajaran Interaktif Agama Hindu Bagi Siswa Kelas VI SD - Saprudin, Usep; Sari, Nanda (Teknik Komputer Politeknik Negeri Sriwijaya, 2025)
Learning Hinduism at SD Negeri 2 Pujo Asri faces the constraints of limited learning resources and a lack of teaching staff. This research aims to develop interactive learning applications to overcome these problems. The Multimedia Development Life Cycle (MDLC) method is implemented through six stages: concept, design, material collection, manufacture, testing, and distribution. This application presents Hindu religious material in interactive multimedia format, including informative text, illustrations, animation, audio, as well as practice questions and quizzes with automatic feedback. The research results show that the use of this application increases students' learning motivation and understanding. Students become more enthusiastic and active in exploring the material, while teachers feel helped in conveying complex concepts. In conclusion, this application can be an innovative solution in improving the quality of Hinduism learning in elementary schools, especially in areas with limited resources, and has the potential to be further developed for other subjects. Keywords: interactive learning, Hinduism, MDLC, multimedia, educational technology.